2022
DOI: 10.3389/fpsyt.2022.902022
|View full text |Cite
|
Sign up to set email alerts
|

Elevated monocyte-to-HDL cholesterol ratio predicts post-stroke depression

Abstract: ObjectivesInflammation plays an important role in the development of depression after stroke. Monocyte-to-HDL Cholesterol Ratio (MHR) recently emerged as a novel comprehensive inflammatory indicator in recent years. This study aimed to investigate whether there is a relationship between MHR levels and post-stroke depression (PSD).MethodsFrom February 2019 to September 2021, patients with acute ischemic stroke (AIS) were recruited within 7 days post-stroke from the two centers and blood samples were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Some scholars found the relevance of this class of inflammatory markers to psychiatric disorders. Such inflammatory markers have also been correlated with depressive disorders [ 35 , 36 ]. In 2021, Sahpolat et al first found significant differences in the MHR between patients with schizophrenia and healthy populations in a small sample study [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars found the relevance of this class of inflammatory markers to psychiatric disorders. Such inflammatory markers have also been correlated with depressive disorders [ 35 , 36 ]. In 2021, Sahpolat et al first found significant differences in the MHR between patients with schizophrenia and healthy populations in a small sample study [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MHR is an indicator of atherosclerosis that evaluates inflammation and dyslipidemia [ 21 ]. As reported, the MHR can help to predict ischemic stroke and related complications [ 22 , 23 ] and is also related to extracranial and intracranial atherosclerotic stenosis [ 7 ]. In this study, it was found that there were differences in MHR, lipid, glucose, liver and renal function levels in subjects with different degrees of carotid plaque, suggesting that there were abnormalities in metabolism in people with carotid plaque.…”
Section: Discussionmentioning
confidence: 99%
“…HDL performs antithrombotic, anti-inflammatory, and antioxidant activities. It protects the endothelium from the harmful effects of LDL and prevents LDL oxidation [ 32 - 34 ]. The monocyte/HDL ratio may be a novel inflammatory and oxidative stress indicator [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It protects the endothelium from the harmful effects of LDL and prevents LDL oxidation. [32][33][34] The monocyte/HDL ratio may be a novel inflammatory and oxidative stress indicator. 16 SII is a new inflammatory biomarker that accurately reflects the balance between inflammation and immune response.…”
Section: Discussionmentioning
confidence: 99%